Language assessment in primary progressive aphasia: Which components should be tested? - Andressa Aguiar da Silva; Marcela Lima Silagi; Karin Zazo Ortiz (PLoS ONE, 2025)
Introduction Primary progressive aphasia (PPA) is a dementia syndrome whose onset and course manifests with language deficits. There is a lack of instruments for clinical assessment of language in dementia and further research in the area is needed. Therefore, the objective of the present study was to identify language tasks that can aid the process of clinically diagnosing PPA and to determine those tasks most impaired in this population. Method A sample of 87 individuals comprising 2 groups was assessed: a PPA group (PPAG) of 29 PPA patients; and a control group (CG) of 58 healthy subjects matched for age and education. All participants underwent a brief cognitive battery followed by a comprehensive language assessment using the MTL-BR Battery. Results A statistically significant performance difference was found between the PPAG and CG on the following tasks: structured interview, oral comprehension of phrases, oral narrative discourse, written comprehension of phrases, written dictation, sentence repetition, semantic verbal fluency, oral naming of nouns and verbs, object manipulation, phonological verbal fluency, body part recognition and left-right orientation, written naming of nouns, oral text comprehension, number dictation, written narrative discourse, written text comprehension and numerical calculations (mental and written). Conclusion The results revealed that performance of PPA patients was poorer compared to healthy subjects on various language tasks. The most useful subtests from the MTL-BR battery for aiding clinical diagnosis of PPA were identified, tasks which should be prioritized when assessing this patient group.